COMPARSION OF CATCHING CHARTS USING INCANDESCENT AND FLUORESCENT LAMPS IN THE LAKE AREA SINGKARAK - Novi D Silaban; Bustari Bustari; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This research was conducted in July - August 2017 at Singkarak Lake, West Sumatera Province. This study aims to determine the ratio of the number of catches chart by using incandescent and fluorescent lamps.The survey method that used to data collection is done by direct observation in field and direct interview with fisherman. This research was conducted for 10 daysnagaritikalaksolok district.The catch during the study was 37.23 kg or 5618 individuals (tails). Based on each catches cart result using Incandescent Lamp is as much as 18.35 kg (2767 individuals (tail)) while using the Neon Lamp is 18.88 kg (2851 individuals (tail)). From the calculation of t test there is significant difference catch chart by using fluorescent lamp either from the amount of weight and the number of individuals caught.Keywords: Catches Chart, Incandescent Lamp, Neon Lamp, Nagari Tikalak.